Chile : Investment Climate Assessment, Volume 1. Executive Summary and Policy Recommendations - World Bank (Washington, DC, 2012)
The Investment Climate Assessment confirms the importance of the investment climate for productivity in Chile. ICA results show that four aspects of the investment climate (business regulation, infrastructure, finance and technology and innovation) affect Chilean firms in terms of their productivity. As may be expected, issues relating to infrastructure and business regulation affect total factor productivity negatively while skills, technology and innovation have a positive impact. The first volume presents the main results of the analysis, including policy recommendations. More in-depth analyses are presented in Volume 2, which is divided into seven chapters. The first chapter provides an overview of the key questions and issues to be discussed and a background on methodology. The second chapter reviews recent economic trends in Chile. The third chapter presents a general statistical overview, including an econometric analysis of the productivity of firms. The remaining chapters provide a detailed analysis of four issues affecting the investment climate: access to and the cost of finance, business and labor regulation, technology and innovation and infrastructure. There is also a technical annex on the econometric methodology.